Modeling and detecting approach for the change point of electronic product infant failure rate. (August 2019) - He, Yihai; Zhao, Yixiao; Wei, Yi; Zhang, Anqi; Zhou, Di
Abstract: Infant failures are the natural enemy of customer satisfaction of electronic product. The change point is a precondition to optimize the burn-in time, warranty period, and root causes in production reliability assurance. However, the method for modeling and detecting the change point is unavailable due to the deficient research on the mechanism of infant failure, thereby hindering the continuous optimization of reliability in this field. Therefore, a quantitative method for modeling and detecting the change point of infant failure rate by using the Weibull distribution is proposed in this paper. Firstly, the mechanism of infant failure and the connotation of the change point of infant failure rate are explained. Then a statistic index is proposed to quantitatively model the trend of change point with the non-constant Weibull shape parameter. Also, the proposed statistic index is adopted to detect the trend of change point by CUSUM chart. Finally, an analysis example of a control board is presented to verify the effectiveness of the proposed approach in detecting the changing trend of infant failure rate for electronic products. Highlights: The connotation of the change point of infant failure rate are explained. A statistic index is proposed to quantitatively model the trend of change point of infant failure. CUSUM chart is adopted to detect the trend of change point of infant failure. The applicability of the proposed method is validated by a control board example.